Posisi Non-Muslim Dalam Hukum Islam : Suatu Tinjauan Atas Pandangan Fakih Klasik - Ayang Utriza Nway (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
One of non-muslim anxieties in the Islamic world is about their status. There treated as second class of citizen of country. And the most difficult problem is why does Islamic law which references to Islam, force to apply for non-muslim, like Christian, Jews, Zoroastrian. This artick attempts to describe about their status in Islamic jurisprudence (fiqh) of Sunni's schools (Hancfi, Maliki, Syafi'i and Hanbali). The artick describes their perspective based on the literature survey which references to main books of those schools in the thouzht of those faqihs.